Autobiographical narratives in major depression: changes in memory specificity during outpatient psychodynamic psychotherapy - Lutz, Magdalena; Nowak, Jonathan; Dönnhoff, Ivo; Friederich, Hans-Christoph; Terhoeven, Valentin; Nikendei, Christoph (BMC psychiatry, 2025)
Previous studies have shown that patients with depression recall fewer specific autobiographical memories, a phenomenon known as overgeneral autobiographical memory (OGM). OGM refers to the retrieval of categorical memories (repeated events) and extended memories (events lasting more than 24 h), rather than specific, single-event recollections. This pattern has been linked to dysfunctional emotion regulation and childhood trauma. While most research has used the Autobiographical Memory Test (AMT) to assess OGM, such standardized cue-word paradigms are limited in capturing how autobiographical memories unfold in real-life psychotherapeutic settings. This study introduces a novel methodology to assess autobiographical memories as they naturally emerge during videotaped psychodynamic psychotherapy sessions.